A Comic Book about the Life and Works of Sabio Caldas (2019)
In commemoration of the birth of Francisco José Caldas, the first Colombian scientist, the historian and cartoonist Alvaro Vélez, also known as Truchafrita, drew the francisco José de Caldas comic book, a path to the stars. This comic is intended to be an instrument of learning in the classroom, so that it is seen and read with the accompaniment of teachers, who can encourage discussions about the discoveries of Francisco José de Caldas